Could hand-eye laterality profiles affect sport performance? A systematic review - Moreno, M.; Capdevila, L.; Losilla, J.-M. (Sports Medicine and Rehabilitation, 2022)
Background Laterality effects on sports performance have been a field of interest for the sports sciences, especially in asymmetrical sports, which require the preferential use of one side of the body. Some sports in particular involve the visual system and ocular laterality, due to the need to clearly focus on a dynamic object (ball, opponent, projectile, etc.). The relationship between manual and ocular laterality results in two perceptual-motor profiles, one where the dominant hand and eye are ipsilateral (uncrossed hand-eye laterality profile, UC-HELP), and the other where they are contralateral (crossed hand-eye laterality profile, C-HELP).